2015
DOI: 10.1111/ans.13032
|View full text |Cite
|
Sign up to set email alerts
|

Marginal artery stump pressure in left colic artery‐preserving rectal cancer surgery: a clinical trial

Abstract: Low ligation with apical lymph node dissection in rectal cancer treatment provides better anastomotic blood supply but is not associated with differences in node retrieval rate or operation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 23 publications
1
92
0
3
Order By: Relevance
“…When further analysis of stage-by-stage OS rates and DFS rates in stage I to stage III cases, there was still no statistically signi cant difference in OS and DFS rates between the LCA preservation group and the LCA non-preservation group in all stage I to stage III. Several previous studies have also shown that, whether preserving LCA or not, there were no signi cant differences with respect to the 5-year mortality in patients underwent laparoscopic rectal cancer, and it seemed to achieve comparable success with acceptable safety outcomes [7][8][9], but data from JCOG0404 showed that preserving LCA, ve-year relapse-free survival and OS tended to be better in the LCA preservation group than the LCA non-preservation group Kaplan-Meier estimates of overall survival and disease-free survival for all anterior resection cases (a and b, respectively). The red line and the green line indicate, respectively, survival curves of the LCA preservation group and the LCA nonpreservation group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When further analysis of stage-by-stage OS rates and DFS rates in stage I to stage III cases, there was still no statistically signi cant difference in OS and DFS rates between the LCA preservation group and the LCA non-preservation group in all stage I to stage III. Several previous studies have also shown that, whether preserving LCA or not, there were no signi cant differences with respect to the 5-year mortality in patients underwent laparoscopic rectal cancer, and it seemed to achieve comparable success with acceptable safety outcomes [7][8][9], but data from JCOG0404 showed that preserving LCA, ve-year relapse-free survival and OS tended to be better in the LCA preservation group than the LCA non-preservation group Kaplan-Meier estimates of overall survival and disease-free survival for all anterior resection cases (a and b, respectively). The red line and the green line indicate, respectively, survival curves of the LCA preservation group and the LCA nonpreservation group.…”
Section: Discussionmentioning
confidence: 97%
“…Retrospective studies suggested that preserving the left colic artery may reduce the incidence of anastomose-related complications but had no effect on the long-term oncologic outcomes [7][8][9]. Nevertheless, preserving the LCA or not during laparoscopic low anterior resection of rectal cancer, is still debated.…”
Section: Introductionmentioning
confidence: 99%
“…Further, patients who underwent further ''re-resection'' up to a ''fluorescent'' portion due to insufficient bowel perfusion in this study were those with left colectomies. With regard to the reason, previous studies found the blood pressure of marginal artery was reduced by ≥30% after the blockage of the left colic artery and unstable blood flow to the left colon occurred after IMA ligation in approximately 10% of patients, which could increase the rate of insufficient perfusion [26][27] . Therefore, we confirmed that insufficient perfusion of the bowel may more frequently occur in patients with left colon cancer, and we should focus more on the bowel perfusion in totally laparoscopic left hemicolectomy, especially for the proximal margin.…”
Section: Postoperative Recovery and Complicationsmentioning
confidence: 99%
“…after the blockage of the left colic artery and unstable blood flow to the left colon occurred after IMA ligation in approximately 10% of patients, which could increase the rate of insufficient perfusion [22][23] . Therefore, we confirmed that insufficient perfusion of the bowel may more frequently occur in patients with left colon cancer, and we should focus more on the bowel perfusion in totally laparoscopic left hemicolectomy, especially for the proximal margin.…”
Section: Postoperative Recovery and Complicationsmentioning
confidence: 99%